PEMBERDAYAAN MASYARAKAT DALAM PERENCANAAN KAWASAN SOSIAL DAN KOMERSIAL BERBASIS EKOWISATA DI PANTAI MATAHARI TERBIT, DESA ADAT SANUR KAJA, DENPASAR, BALI - Putra, Ida Bagus Gede Parama; Putra, Ida Bagus Udayana; Putri, Ni Putu Ratih Pradnyaswari Anasta (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
Matahari Terbit Beach in Sanur plays a vital role in the lives of the local community, both as a popular tourist destination and as a location for traditional ceremonies such as ngaben. However, zoning changes due to the relocation of the Sanur port have presented significant challenges, including a decline in revenue for vendors along the beach and a lack of nighttime tourist attractions. This community service project aims to develop a master plan that integrates the cultural, social, and economic needs of the local community with sustainable tourism potential. The methods used include field surveys, data analysis, and Focus Group Discussions (FGD) with the local community to produce environmentally friendly and sustainable area designs. The planning outcomes include the reorganization of the commercial area, the utilization of reclaimed land for social facilities, and the development of a multifunctional pavilion (wantilan). This concept is expected to improve the quality of life for the community, strengthen the local economy, and maintain the balance of the local ecosystem and culture. The more integrated area planning is intended to serve as a reference for sustainable development at Matahari Terbit Beach, ensuring that the area continues to function as a center for traditional activities and an attractive tourist destination.